2018
DOI: 10.1097/jxx.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy: A discussion and case study

Abstract: The advanced practice nurse (APN) is instrumental in differentiating between TCM versus acute myocardial infarction, heart failure, pulmonary edema, dynamic outflow obstruction, and cardiogenic shock. Because of these possible acute and critical presentations, prompt recognition and intervention for patients with TCM are priorities for nurse practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Further studies report cases of patients presenting to the emergency department whose diagnosis was confused with AMI due to similar symptoms, relating to chest pain and dyspnea; it has been shown that diagnostic and treatment errors are often present in these situations, and that healthcare personnel training is necessary to prevent emergency situations with non-specific and inadequate treatments [ 1 , 6 , 11 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further studies report cases of patients presenting to the emergency department whose diagnosis was confused with AMI due to similar symptoms, relating to chest pain and dyspnea; it has been shown that diagnostic and treatment errors are often present in these situations, and that healthcare personnel training is necessary to prevent emergency situations with non-specific and inadequate treatments [ 1 , 6 , 11 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Takotsubo cardiomyopathy (TCM), also called stress cardiomyopathy (SC) or stress-induced cardiomyopathy, is a reversible heart disease that mimics the symptoms of an acute myocardial infarction (MI or AMI). An MI is the result of ischemia due to blockage of the coronary vessels, whereas in TCM there is no blockage of the vessels [ 1 3 ]. It is an atypical pattern of abnormalities of parietal kinetics such as excessive anomalous movement of the basal wall with medio-ventricular and apical hypokinesia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations